2019
DOI: 10.1080/03736687.2019.1626167
|View full text |Cite
|
Sign up to set email alerts
|

The effects of winter stress on Sphagnum species with contrasting macro- and microdistributions

Abstract: Introduction. Sphagnum L. forms much of the ground cover in northern peatlands. Different species show affinities for bioclimatic regions in Europe (oceanic/continental; northern/ southern) and species-specific tolerance of winter conditions can be a factor explaining their distribution. Methods. We focussed on low temperature in a series of experiments and tested (1) the innate ability of a selection of Sphagnum species to tolerate low temperature in relation to their microtopographic (wetness) and geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
4
2
Order By: Relevance
“…Fen bryophytes have shown negative response in Fv/Fm to snow removal (Kuttim et al, 2019), which is in contrast to our results and indicative of habitat-specific responses to winter climate change as also observed among Sphagnum species (Campbell & Rydin, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Fen bryophytes have shown negative response in Fv/Fm to snow removal (Kuttim et al, 2019), which is in contrast to our results and indicative of habitat-specific responses to winter climate change as also observed among Sphagnum species (Campbell & Rydin, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…The potential activity of summer photosystem II (Fv/Fm) was enhanced for many of the tested species to various extreme event treatments indicating that this part of the photosynthetic apparatus appears to benefit, and may influence cryptogam capability to cope with extreme winter climatic events. Fen bryophytes have shown negative response in Fv/Fm to snow removal (Kuttim et al, 2019), which is in contrast to our results and indicative of habitat‐specific responses to winter climate change as also observed among Sphagnum species (Campbell & Rydin, 2019). Hydration status greatly affects seasonal variation in moss CO 2 flux rates with largest variation among hydric mosses (Davey & Rothery, 1996) which is in line with the contrasting response between Hylocomium versus Polytrichum and Racomitrium .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In the north, seasonal variation is caused by low temperatures during winter and late autumn (before snow cover gives protection). Comparing species occupying similar micro-habitats, northern species in general tolerate such conditions better than their southern counterparts (Campbell and Rydin 2019).…”
Section: The Relationship Between Climate and Sphagnum Species Distributionmentioning
confidence: 99%
“…Even though Sphagnum species have effective long-distance dispersal (Sundberg 2010(Sundberg , 2013, they vary in their distribution in Europe from south to north and from oceanic to continental areas. Experiments have indicated that northern species of Sphagnum tolerate cold autumns and winters better than species with more southern distribution (Campbell and Rydin 2019). There is also a large variation in drought resistance and growth response to temperature among Sphagnum species (Breeuwer et al 2008, Rydin andJeglum 2013).…”
Section: Introductionmentioning
confidence: 99%